2017
DOI: 10.5194/bg-14-2019-2017
|View full text |Cite
|
Sign up to set email alerts
|

Timescale dependence of environmental controls on methane efflux from Poyang Hu, China

Abstract: Abstract. Lakes are an important natural source of CH4 to the atmosphere. However, the multi-seasonal CH4 efflux from lakes has been rarely studied. In this study, the CH4 efflux from Poyang Hu, the largest freshwater lake in China, was measured monthly over a 4-year period by using the floating-chamber technique. The mean annual CH4 efflux throughout the 4 years was 0.54 mmol m−2 day−1, ranging from 0.47 to 0.60 mmol m−2 day−1. The CH4 efflux had a high seasonal variation with an average summer (June to Augus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 86 publications
(114 reference statements)
1
5
1
Order By: Relevance
“…This research clearly demonstrated that the subdaily dynamics of diffusive CH 4 emission from a shallow lake was controlled by the transfer efficiency at the air‐water interface as well as the water mixing and resulting transfer of dissolved CH 4 in the bottom water layer accumulated during the preceding period to the surface water. The wind speed dependence of the observed diffusive flux (Figure 5) was consistent with previous studies, including floating chamber observations in Liu et al (2017) and gas‐transfer velocity studies (Guérin et al, 2007; Heiskanen et al, 2014). Subsurface turbulence is enhanced by increasing wind speed (e.g., Wanninkhof et al, 2009), which explains the dependence of diffusive flux on wind speed.…”
Section: Discussionsupporting
confidence: 90%
“…This research clearly demonstrated that the subdaily dynamics of diffusive CH 4 emission from a shallow lake was controlled by the transfer efficiency at the air‐water interface as well as the water mixing and resulting transfer of dissolved CH 4 in the bottom water layer accumulated during the preceding period to the surface water. The wind speed dependence of the observed diffusive flux (Figure 5) was consistent with previous studies, including floating chamber observations in Liu et al (2017) and gas‐transfer velocity studies (Guérin et al, 2007; Heiskanen et al, 2014). Subsurface turbulence is enhanced by increasing wind speed (e.g., Wanninkhof et al, 2009), which explains the dependence of diffusive flux on wind speed.…”
Section: Discussionsupporting
confidence: 90%
“…The previous studies on full, 24-h methane flux cycles are limited and although some of them also demonstrated diel CH 4 patterns, the findings were not consistent (12)(13)(14)(15)(16)(17)(18)(19). Some of these studies rely on flux modeling from surface water concentrations and wind speed.…”
mentioning
confidence: 95%
“…At the shallowest station (Ulvhällsfjärden) during August surface water was 20.6°C and the deepest waters (9 m) were 18.4°C. Thus, at the stations with shallow waters the sediments will be warmer during summer, favoring seasonal increases in CH 4 production and we note that others have shown that bottom water temperatures in very large lakes do relate to surface CH 4 emissions (Fernandez et al, 2020;Liu et al, 2017). However, although shallower, warmer stations tended toward higher summertime CH 4 , there was not a significant correlation between bottom water temperature and CH 4 (Figure 4b) suggesting that other drivers are also involved.…”
Section: Spatial and Seasonal Variations In Chmentioning
confidence: 63%
“…However, a clear outlier occurred at this time, with the shallow‐water Västeråsfjärden station having the highest CH 4 concentration measured during the entire study (5.39 μg l −1 ) (Figure 3). This was despite cold temperatures (mean surface water 2.3°C) which would be expected to decrease CH 4 production rates (Fernandez et al., 2020; Liu et al., 2017). Without analytical replicates (see Section 2.2) we cannot fully eliminate the possibility that this value relates to analytical or sampling error.…”
Section: Resultsmentioning
confidence: 99%